Intercultural Learning in Transnational Articulation Programs: The Hidden Agenda of Chinese Students’ Experiences - Dai, Kun; Garcia, Jaime (Journal of International Students, 2019)
Many Chinese universities engage in transnational higher education by establishing articulation programs with international partners. Although research has broadly investigated transnational higher education topics, few studies have explored Chinese students’ intercultural learning and adjustment experiences in these programs. This qualitative study explored seven Chinese students’ experiences in two China-Australia articulation programs to add insights to this under-researched topic. The findings indicated that research participants’ intercultural learning experiences were far more complex than the theoretical model of “stress-adaptation-development.” The students’ agency, identity, and belonging underwent dynamic changes due to academic inconsistencies and differences, including the use of technology, assessment, and teaching strategies. This study suggests that it is important for educators to consider educational differences in designing and implementing transnational articulation programs.